2022
DOI: 10.1002/jsf2.70
|View full text |Cite
|
Sign up to set email alerts
|

The functions and applications of GDSL esterase/lipase proteins in agriculture: A review

Abstract: GDSL esterase/lipase proteins (GELPs) compose a family of enzymes identified by a unique “GDSL” amino acid sequence motif. GELPs can accept a broad range of substrates and are functionally diverse. They are involved in various key physiological processes in plants such as cuticle development, seed oil storage, male fertility, and biotic and abiotic stress responses. Thus, genetic manipulation of GELPs has the potential to be beneficial in agriculture. As examples, the Seed Fatty Acid Reducer proteins in rapese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…The abovementioned results showed that the expression of the marker genes GDSL-1 and GDSL-2 was upregulated in cluster 11. Earlier research confirmed GDSLs are lipid hydrolytic enzymes with broad substrate specificity, such as acetyl and butyl esterase, sinapine esterase, fatty acylester hydrolase, and triacylglycerol (TAG) hydrolase (Akoh et al, 2004;Aparato & Suh, 2022;Lee et al, 1997). As an important energy source in plants, reserve lipids are stored as TAG in oil bodies, which are formed in the endoplasmic reticulum (Murphy, 2012).…”
Section: Overexpression Of Gdsl Accelerated the Hydrolysis Of Triacyl...mentioning
confidence: 99%
“…The abovementioned results showed that the expression of the marker genes GDSL-1 and GDSL-2 was upregulated in cluster 11. Earlier research confirmed GDSLs are lipid hydrolytic enzymes with broad substrate specificity, such as acetyl and butyl esterase, sinapine esterase, fatty acylester hydrolase, and triacylglycerol (TAG) hydrolase (Akoh et al, 2004;Aparato & Suh, 2022;Lee et al, 1997). As an important energy source in plants, reserve lipids are stored as TAG in oil bodies, which are formed in the endoplasmic reticulum (Murphy, 2012).…”
Section: Overexpression Of Gdsl Accelerated the Hydrolysis Of Triacyl...mentioning
confidence: 99%